2016
DOI: 10.1523/jneurosci.2880-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Bulb Deep Short-Axon Cells Mediate Widespread Inhibition of Tufted Cell Apical Dendrites

Abstract: In the main olfactory bulb (MOB), the first station of sensory processing in the olfactory system, GABAergic interneuron signaling shapes principal neuron activity to regulate olfaction. However, a lack of known selective markers for MOB interneurons has strongly impeded cell-type-selective investigation of interneuron function. Here, we identify the first selective marker of glomerular layer-projecting deep short-axon cells (GL-dSACs) and investigate systematically the structure, abundance, intrinsic physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 59 publications
0
56
0
Order By: Relevance
“…The results of our survey of JGCs revealed the presence of two JGC subpopulations with macroscopically similar in their intrinsic physiological features to PG subsets in the MOB (Puopolo and Belluzzi, 1998;Murphy et al, 2005;Sethupathy et al, 2013;Najac et al, 2015;Burton et al, 2017) (Figs. 6-7).…”
Section: Aob Jgcs Include Physiologically-distinct Subsets Associatedmentioning
confidence: 79%
See 1 more Smart Citation
“…The results of our survey of JGCs revealed the presence of two JGC subpopulations with macroscopically similar in their intrinsic physiological features to PG subsets in the MOB (Puopolo and Belluzzi, 1998;Murphy et al, 2005;Sethupathy et al, 2013;Najac et al, 2015;Burton et al, 2017) (Figs. 6-7).…”
Section: Aob Jgcs Include Physiologically-distinct Subsets Associatedmentioning
confidence: 79%
“…The MOB has several interneuron types, collectively termed JGCs, which reside in and around the glomerular layer (Larriva-Sahd, 2008;Yokosuka, 2012). In the MOB, JGCs include excitatory external tufted cells, several types of inhibitory periglomerular cells, and short axon cells (Shipley and Ennis, 1996;Schoppa et al, 1998;Aungst et al, 2003;Parrish-Aungst et al, 2007;Shao et al, 2009;Liu et al, 2013;Najac et al, 2015;Burton et al, 2017;Geramita and Urban, 2017). In the AOB, very few electrophysiological inquiries have been undertaken on JGCs (Goldmakher and Moss, 2000;Hu et al, 2016).…”
Section: Electrophysiological Characteristics Of Aob Jgcsmentioning
confidence: 99%
“…; Burton et al . ) and are themselves modulated by basal forebrain inputs. This diversity of olfactory bulb interneurons under the control of basal forebrain fibres makes it challenging to predict the global functional implications of this GABAergic innervation on the olfactory bulb output.…”
Section: Discussionmentioning
confidence: 99%
“…; Burton et al . ) whereas superficial SA cells are tyrosine hydroxylase (TH)‐expressing mixed dopaminergic/GABAergic neurons that regulate glutamate release from OSNs and monosynaptically inhibit external tufted cells (Liu et al . ; Whitesell et al .…”
Section: Introductionmentioning
confidence: 99%
“…The spontaneous IPSC frequency was only modestly reduced in visualized MCs with apical dendrites truncated before reaching the glomerular layer, compared with intact MCs, suggesting that most of the inhibitory tone detected in somatic recordings from OB principal cells originates from interneurons outside of the glomerular layer, presumably GCs. While several populations of non-GC interneurons exist in the GCL, these appear to target either TCs (GL-dSACs, 53) or GCs (25, 54). A recent study (55) has found that parvalbumin (PV)-positive interneurons located in the EPL form reciprocal synapses with MCs and, therefore, could also contribute to the inhibitory synchrony we observe.…”
Section: Discussionmentioning
confidence: 99%